Contemporary Pathological Stage Distribution After Radical Prostatectomy in North American High-Risk Prostate Cancer Patients - Chierigo, Francesco; Borghesi, Marco; Würnschimmel, Christoph; Flammia, Rocco Simone; Sorce, Gabriele; Hoeh, Benedikt; Hohenhorst, Lukas; Tian, Zhe; Saad, Fred; Tilki, Derya; Gallucci, Michele; Briganti, Alberto; et al. (Clinical genitourinary cancer, 2022)
PURPOSE: To investigate pathological stage at radical prostatectomy (RP) using the "Partin tables" approach in NCCN high-risk (HR) prostate cancer (PCa) patients. MATERIALS AND METHODS: Within the SEER 2010 to 2016 database, we identified 7,718 NCCN HR PCa patients. Cross-tabulation was used to illustrate the distribution of organ confined disease (OC, pT2), extra-prostatic extension (EPE, pT3a), seminal vesicles invasion (SVI, pT3b), lymph node invasion (LNI, pT2N1), extra-prostatic and lymph node invasion (EPE + LNI, pT3aN1), and seminal vescicale and lymph node invasion (SVI + LNI, pT3bN1), according to preoperative criteria, which consisted in PSA, clinical T stage, biopsy Gleason Score (GS). Binomial 95%CI was constructed for the reported proportions. RESULTS: Median (IQR) PSA levels was 9 (6-20) ng/ml. The majority of patient harbored cT1c (51%) followed by cT2 (35%) and cT3 (14%) stage. Most patients exhibited GS 4+4 (43%). Overall, 87 vs. 15 vs. 2% of patients harbored only 1 vs. 2 vs. all 3 HR criteria. At RP, OC, EPE, SVI, and LNI rates were respectively 36%, 27%, 17%, and 19%. Highest levels of OC were recorded for cT1c, PSA <10 ng/mL and biopsy GS4+4. Conversely, EPE, SVI and LNI were the highest in patients with cT3, PSA ≥20 ng/mL and GS 5+5. After stratification according to clinical stages, OC rates decreased with increasing PSA levels and GS. Conversely, EPE, SVI and LNI rates increased with increasing PSA and GS. CONCLUSION: We provide a lookup table to illustrate the relationship between clinical and pathological characteristics in NCCN HR PCa patients.
Keywords: Male; Seminal Vesicles; Neoplasm Staging; semenné váčky; Prostatic Neoplasms; mužské pohlaví; prostatektomie; SEE; High-risk prostate cancer; prostatický specifický antigen; lidé; Staging; Humans; nádory prostaty; North America; Partin tables; Prostatectomy; staging nádorů; Prostate-Specific Antigen; Lookup table; Severní Amerika